Efeito da resistência ao cisalhamento do concreto na flexão de lajes de concreto armado - Rocha, Mércurie Janeai Mateus Araujo (2017)
In this work the influence of the shear strength of the concrete in the bending of reinforced concrete slabs was studied through two models of analysis. The first model (proposed model 1) combines an isotropic damage model for concrete, proposed by Oliver et al., and the perfect elastoplastic model for steel reinforcement. The second model (proposed model 2), which is in fact a modification of the previous model, introduces a unique damaging to the concrete transverse modulus of elasticity, based on a proposal by Matzenbacher. The behavior of slabs was simulated through the Classical Theory of Laminates and the variational formulation of the problem was developed through the Principle of Virtual Works. The numerical treatment of the problem was based on the Finite Element Method, using a finite rectangular element with 24 degrees of freedom, incorporating Newton-Raphson's incremental-iterative process with load control and displacement control. The validation of the two models was based on the simulation of four rectangular slabs under bending, whose analysis revealed that it is essential to damage the concrete modulus of elasticity when using the damage mechanics.